Studi Eksperimental Variasi Komposisi Fly Ash dan Abu Batu Andesit Terhadap Kuat Tekan Mortar Geopolimer - Nanda Agustin; Tira Roesdiana (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Geopolymers are one of the innovative materials currently being developed as a substitute for portland cement as a binder. CoMPared to Portland cement-based mortar, geopolymer mortar offers advantages such as relatively low carbon emissions, competitive compressive strength potential, and good chemical resistance. The method used in this study involved test specimens measuring 5 × 5 × 5 cm3 using room temperature curing. The binder mixtures used consisted of fly ash and andesite ash, with five different ratios: 70% FA : 30% ABA; 50% FA : 50% ABA; 30% FA : 70% ABA; 0% FA : 100% ABA and 100% FA : 0% ABA. The activator solution used a ratio of Na2SiO3 : NaOH ratio of 2,5 : 1 with an 8 mol/L NaOH concentration. This study aimed to determine the optimum percentage ratio of fly ash and andesite ash mixture. The results showed that differences in binder composition affect the compressive strength of the geopolymer mortar. The optimum compressive strength of all test specimen variations was obtained in the 70% FA : 30% ABA variation, at 17,07 MPa at 28 days. These findings indicate that fly ash can accelerate the geopolymerization process, while andesite ash function as an additive that helps make the mortar structure denser.